2014
DOI: 10.1098/rspb.2014.0489
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epistasis on sexually antagonistic genetic variation

Abstract: There is increasing evidence of segregating sexually antagonistic (SA) genetic variation for fitness in laboratory and wild populations, yet the conditions for the maintenance of such variation can be restrictive. Epistatic interactions between genes can contribute to the maintenance of genetic variance in fitness and we suggest that epistasis between SA genes should be pervasive. Here, we explore its effect on SA genetic variation in fitness using a two locus model with negative epistasis. Our results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 63 publications
2
55
0
Order By: Relevance
“…IaSC occurs when selection favors alternative alleles in males and females at a given locus (Rice 1992;Chippindale et al 2001) and can act to maintain standing genetic variation with sexually antagonistic (SA) effects on fitness (Kidwell 1977;Connallon and Clark 2012;Arnqvist et al 2014). As a consequence, the degree of SA genetic variation in well-adapted populations may be large relative to genetic variation for overall viability.…”
Section: Introductionmentioning
confidence: 99%
“…IaSC occurs when selection favors alternative alleles in males and females at a given locus (Rice 1992;Chippindale et al 2001) and can act to maintain standing genetic variation with sexually antagonistic (SA) effects on fitness (Kidwell 1977;Connallon and Clark 2012;Arnqvist et al 2014). As a consequence, the degree of SA genetic variation in well-adapted populations may be large relative to genetic variation for overall viability.…”
Section: Introductionmentioning
confidence: 99%
“…; Miller and Svensson ), and epistasis (Arnqvist et al. ) among other possible mechanisms. Context‐specific fitness can include spatially (Johnson et al.…”
mentioning
confidence: 99%
“…The expectation that directional selection should remove variation from populations has long been at odds with the observation that there is abundant variation for fitness-related traits (Barton 1990;Houle 1998;Johnson and Barton 2005). There are many hypothesized mechanisms for the maintenance of variation: balancing selection (Connallon and Clark 2014), sexually antagonistic selection (Foerster et al 2007), context-specific fitness (Mojica et al 2012;Miller and Svensson 2014), and epistasis (Arnqvist et al 2014) among other possible mechanisms. Context-specific fitness can include spatially (Johnson et al 2013) or temporally varying selection (Bergland et al 2014) and social or sexual selection (Lyon and Montgomerie 2012).…”
mentioning
confidence: 99%
“…They found that the simultaneous action of these selection pressures at two linked loci expanded the opportunity for polymorphism relative to what is predicted from single‐locus models. Further, as has been shown in other autosomal two‐locus models (Úbeda et al ., ; Patten et al ., ; Arnqvist et al ., ; Haig et al ., ), linkage disequilibrium (LD) accompanied any polymorphic equilibrium. Finally, Patten () showed that the occurrence of drive with sexual antagonism on an autosome favoured reduced recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Several forms of natural selectionfor example, antagonistic selection, fluctuating selection and heterozygote advantagehave been recognized for their purported roles in maintaining population genetic variation, and particular attention has been given to assessing which of these forms is most likely to account for variation found in nature (Prout, 2000). Additionally, several genetic properties, including dominance (Owen, 1953;Kidwell et al, 1977;Fry, 2010), interaction with other genes (Patten et al, 2010;Arnqvist et al, 2014;Haig et al, 2014) and transmission routes (Haldane, 1924(Haldane, , 1926Rice, 1984Rice, , 1998Hedrick & Parker, 1997;Patten & Haig, 2009a,b;Jordan & Charlesworth, 2012;Santure & Spencer, 2012), have been examined for their influence on population genetic variation. Over time, a picture has emerged of how natural selection and the genetic system combine to shape patterns of polymorphism.…”
Section: Introductionmentioning
confidence: 99%